2000
DOI: 10.1007/pl00004179
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Oral Disodium Pamidronate in Established Osteoporosis: A 2 Year Double-Masked Placebo-Controlled Study of Efficacy and Safety

Abstract: The effect of oral pamidronate on bone mineral density and its adverse effect profile was investigated by a double-masked placebo-controlled study of 122 patients aged 55-75 years with established vertebral osteoporosis. Patients on active therapy received disodium pamidronate 300 mg/day (group A) for 4 weeks every 16 weeks, 150 mg/day (group B) for 4 weeks every 8 weeks or placebo (group C). All patients additionally received 500 mg of calcium and 400 IU vitamin D daily. Dual-energy X-ray absorptiometry measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
2

Year Published

2000
2000
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 29 publications
2
7
0
2
Order By: Relevance
“…30 Nitrogen-containing bisphosphonates have also been given intermittently, usually with drug-free intervals of 3 months. [45][46][47][48][49][50][51] However, in no such study was fracture incidence assessed.…”
Section: Bisphosphonate Dosing At Extended Drug-free Intervalsmentioning
confidence: 99%
“…30 Nitrogen-containing bisphosphonates have also been given intermittently, usually with drug-free intervals of 3 months. [45][46][47][48][49][50][51] However, in no such study was fracture incidence assessed.…”
Section: Bisphosphonate Dosing At Extended Drug-free Intervalsmentioning
confidence: 99%
“…Pamidronate has been used for many years in Leiden as a model compound to study the action and efficacy of nitrogen‐containing bisphosphonates (9–12) and was the first bisphosphonate of this class to be given to patients with osteoporosis (13,14) . Various modes of administration of oral or intravenous pamidronate were shown to prevent bone loss in patients with postmenopausal, idiopathic and glucocorticoid‐induced osteoporosis in open or controlled studies (13–20) . Early open studies suggested, in addition, that daily oral pamidronate induces a significant increase in bone mineral density of the spine (LS‐BMD) that is not confined to the first 2 years of therapy, as expected from an antiresorptive agent, but continues for at least 4 years of continuous treatment (14,21) .…”
Section: Introductionmentioning
confidence: 99%
“…Six publications were excluded because they reported on total number of fractures and the number of patients with at least one fracture was not published and could not be derived from published data [34, 46,73,76,80,85]. Sixteen publications were excluded because the duration of observation was less than 36 months [5,7,15 [61] had a median duration of only 21 months, but was kept in the final analysis as it was stopped early by the sponsor.…”
Section: Resultsmentioning
confidence: 99%